2022
DOI: 10.3390/cancers14133094
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Challenges in Uveal Melanoma Immunotherapy

Abstract: Uveal melanoma (UM) is the most common primary intraocular malignancy in adults. Compared to cutaneous melanoma (CM), which mainly harbors BRAF or NRAS mutations, UM predominantly harbors GNAQ or GNA11 mutations. Although primary UM can be controlled locally, approximately 50% of patients still develop metastases. To date, there have been no standard therapeutic strategies for the prevention or treatment of metastases. Unfortunately, chemotherapy and targeted therapies only induce minimal responses in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 184 publications
0
18
0
Order By: Relevance
“…Focal radiation therapy, including proton-beam radiation therapy, is a commonly used treatment modality to rescue the eye and can achieve high tumor control rates in over 90% of patients ( 2 ). Whereas primary UM can get local control, 50% of UM will eventually metastasize ( 6 ). Both uveal melanoma and cutaneous melanoma originate from melanocytes, but there are significant differences in their pathological features and treatment outcomes ( 1 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Focal radiation therapy, including proton-beam radiation therapy, is a commonly used treatment modality to rescue the eye and can achieve high tumor control rates in over 90% of patients ( 2 ). Whereas primary UM can get local control, 50% of UM will eventually metastasize ( 6 ). Both uveal melanoma and cutaneous melanoma originate from melanocytes, but there are significant differences in their pathological features and treatment outcomes ( 1 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The eye is an immune-privileged organ giving a growth advantage to primary UM, and immune privilege may be responsible for immune evasion and systemic metastasis ( 2 , 6 ). Given the immunosuppressive microenvironment of UM ( 6 ), it is important to understand the link between risk scores and immunological characteristics of UM samples. Our study identified a clear difference in immune cell infiltration among high- and low-risk groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific aspects of choroidal microenvironment participate in the physiological mechanisms that the eye uses to give tumor metastases a growth advantage as an immunologically privileged organ [ 27 ]. A recent study showed that this immune-privileged microenvironment limited the effectiveness of immunotherapy in an intraocular metastasis mouse model.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Uveal melanoma (UVM) is the most common primary intraocular malignancy in adults (85%) and is highly malignant, invasive, and extremely metastatic with a poor prognosis [ 1 , 2 ]. In current practice, the first-line treatment of primary uveal melanoma is local ocular treatment, including plaque brachytherapy, local resection, and enucleation [ 3 ]. Over the last 5 years, novel prognostic biomarkers have been identified, including histone deacetylase HDAC-2 [ 4 ], DNA damage response protein ATR [ 5 ], and genes of the NF-κB pathway [ 6 ].…”
Section: Introductionmentioning
confidence: 99%